The abundance and habitat use of demersal fishes on a rocky offshore bank using the ROPOS remotely operated vehicle. (March 2020) - Tolimieri, N.; Clarke, M.E.; Clemons, J.; Wakefield, W.; Powell, A.
Abstract: Offshore rocky banks are ecologically important refuge habitats for a number of U.S. commercial groundfish species. However, they are challenging to survey, and data on the abundance and ecology of fish populations at deep banks are limited. We used the remotely operated vehicle ROPOS to carry out visual surveys at two sites on Cherry Bank in the Southern California Bight, eastern Pacific Ocean. We observed differences in fish assemblages related to depth and habitat type and found that rockfishes ( Sebastes spp) made up 65% of fishes recorded. Rockfishes and combfish ( Zaniolepis spp) were associated with relatively shallow areas with hard substrate whereas flatfishes (Pleuronectiformes) and poachers (Agonidae) were found on unconsolidated sediments. Thornyheads ( Sebastolobus spp) and hagfishes (Myxinidae) mainly occurred in areas of patchy habitat. Habitat and depth explained 52% of the variation in fish assemblages between transects with habitat explaining a greater proportion of the variation than depth. We observed large differences in the number of juvenile rockfishes and Sebastomus rockfishes between study sites with hard substrates and also had higher abundances of juvenile rockfishes versus sites characterized by mixed substrates. With the exception of unidentified Sebastomus, the current design had relatively low power to reliably detect observed differences for most taxa, so we report the number of additional transects that would be required to detect a 50% increase in densities. These data provide a baseline on groundfish densities and habitat associations at Cherry Bank and key information for the design of future work including Bayesian approaches to estimating coast-wide abundance. Highlights: ROPOS ROV was used to survey fish assemblages at Cherry Bank. Rockfishes ( Sebastes spp) made up 65% of fishes recorded. Habitat and depth explained 52% of the variation in fish assemblages. Habitat was more important than depth in determining fish assemblages. Juvenile rockfishes were much more common on hard substrates than on mixed ones.